Photosynthetic performance of spring maize leaves and the development and formation of superior and inferior grains - Cao, Wenzhuo; Yu, Zhenwen; Shi, Yu; Zhang, Zhen; Zhang, Yongli (Frontiers in Plant Science, 2026)
IntroductionNitrogen application is crucial for enhancing maize yield and optimizing grain filling. However, the effects of nitrogen fertilization on post–anthesis leaf photosynthetic performance, starch accumulation dynamics in superior and inferior grains, grain development, and yield remain unclear. MethodsA field experiment with five nitrogen fertilization rates (0 [N0], 90 [N90], 135 [N135], 180 [N180], and 225 [N225] kg ha–1) was conducted in the black soil region of Northeast China during the spring maize growing seasons of 2022 to 2024.ResultsCompared with the other treatments (N0, N90, N135, and N225), the N180 treatment significantly increased the activities of superoxide dismutase (SOD) and peroxidase (POD) in ear leaves after anthesis, optimized the balance between zeatin riboside (ZR) and abscisic acid (ABA), delayed leaf senescence, and thereby increased the net photosynthetic rate by 1.8–76.6%. Meanwhile, compared to the other treatments, the N180 treatment enhanced the activities of ADP–glucose pyrophosphorylase (AGPase) and soluble starch synthase (SSS) in both superior and inferior grains by 7.7–49.3% and 7.4–36.9%, respectively, compared with the N0, N90, N135, and N225 treatments. This improvement optimized the endogenous hormone balance in grains, increased starch accumulation rates in both superior and inferior grains, prolonged the active starch accumulation period, and promoted grain filling. The synergistic improvement in source leaf photosynthetic performance and grain sink activity ultimately enabled the N180 treatment to coordinately increase the kernel number per ear and 100–kernel weight, resulting in a yield increase of 5.8–55.7% compared with the N0, N90, N135, and N225 treatments. DiscussionFuture studies may further reveal the physiological and molecular mechanisms by which nitrogen coordinates source–sink functions from perspectives such as hormonal signaling and the regulation of key enzyme gene expression.